Pengaruh Keterampilan Kewirausahaan terhadap Keberhasilan Bisnis Startup Berbasis Teknologi Informasi (Indo-MathEdu Intellectuals Journal, 2025)
The development of technology-based startups in Indonesia has shown rapid growth; however, the failure rate remains relatively high. One of the key factors influencing startup success is the entrepreneurial skills possessed by the founders. This study aims to analyze the influence of entrepreneurial skills on the success of technology-based startups in Indonesia. The research uses secondary data obtained from scientific journals, books, research reports, and other relevant publications. A descriptive qualitative approach was employed with content analysis techniques to identify concepts, patterns, and relationships between variables from various literature sources. The results show that skills such as innovation, adaptability to change, risk management, and the ability to build strategic networks significantly impact startup success. These abilities enable startup founders to design flexible business models in the face of market uncertainty and to build effective work teams. This study recommends strengthening the digital entrepreneurship ecosystem through training, mentoring, and supportive policies as strategies to enhance the success of technology startups in Indonesia.